2014
DOI: 10.1103/physreve.89.063307
|View full text |Cite
|
Sign up to set email alerts
|

Boundary conditions for surface reactions in lattice Boltzmann simulations

Abstract: A surface reaction boundary condition in multicomponent lattice Boltzmann simulations is developed. The method is applied to a test case with nonlinear reaction rates and nonlinear density profiles. The results are compared to the corresponding analytical solution, which shows that the error of the method scales with the square of the lattice spacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…( 5) need to be transformed into expression in the LB model. Several LB boundary conditions have been developed for surface reaction [8,[44][45][46][47]. The one proposed by Kang et al [44] is adopted.…”
Section: Lb Boundary Conditions For Surface Reactionmentioning
confidence: 99%
“…( 5) need to be transformed into expression in the LB model. Several LB boundary conditions have been developed for surface reaction [8,[44][45][46][47]. The one proposed by Kang et al [44] is adopted.…”
Section: Lb Boundary Conditions For Surface Reactionmentioning
confidence: 99%
“…When two or more reactions occur simultaneously, Kang et al [2007] and Hiorth et al [2013] have shown an iterative method. However, Gillissen and Looije [2014] recently proposed an explicit method based on Taylor expansion to replace the iterative procedure and we use this method in our work.…”
Section: Chemical Reactionsmentioning
confidence: 99%
“…In addition to the CDE coupled with the Navier-Stokes (NS) equation, boundary conditions are necessary for completing the mathematical description of a system involving heat and mass transfer. In particular, complicated boundary conditions are widely encountered in heat and mass transfer systems, such as the Neumann condition at the adiabatic boundary [34] and conjugate interfaces [35][36][37][38][39][40][41], the linear and nonlinear Robin conditions for surface reactions [42,43], adsorption kinetics [44], and radiative heat transfer process [45]. Therefore, boundary implementations in accordance with the macroscopic boundary constraints are crucially important for the accuracy and efficiency of the CDE LB simulations.…”
Section: Introductionmentioning
confidence: 99%